Impact of Fluid Team Performance on Strategic HRM : An Empirical Study in the Organized Retail Sector of West Bengal - Giri, Arunangshu; Chatterjee, Satakshi (Prabandhan: Indian Journal of Management, 2020)
Background : The growth of the organized retail sector is exponential. Hence, a huge boost has been observed in the demand of the organized retail segment. This demand could be met with the utilization of the fluid teams as they consist of various team members who have a rich knowledge pool from diverse fields which could be assembled under a singular structure by the human resource department. Purpose : This study attempted to examine the impact of identified relevant factors on the fluid team performance and consequently on the effectiveness of HRM strategies through structural modeling. Research Methodology : Primary data were collected from the various employees working in several retail stores. Secondary data were collected from various research articles wherein similar studies have been conducted. Various statistical tools like exploratory factor analysis (EFA), confirmatory factor analysis (CFA), and structural equation modeling (SEM) were executed in this study by using SPSS 23 and AMOS 23 software. Findings : Various factors such as Creative Process, Inflexible Communication Process, Conflict Management Process, and Team Management Process had a positive impact on the fluid team performance which led to effective HRM strategies. Research Limitations : This study was limited to the area of West Bengal, India. The outcomes may vary in the global context. This research basically lays the foundation of future research in this field. Managerial Implications : Fluid teams could be proven to be very helpful in terms of the achievement of the organization’s goal by selecting the most influencing factors pertaining to strategic decision making.